Corrosion prevention of crude and vacuum distillation column overheads in a petroleum refinery: A field monitoring study. Issue 2 (24th October 2020) - Subramanian, Chidambaram
Abstract: The aim of the present work is to monitor dew point corrosion of crude and vacuum distillation column overhead section in a petroleum refinery. The material of construction of overhead line pipe was carbon steel. The state of art of crude unit process was introduced. The corrosion and associated hydrolyzing mechanisms were briefly described. The crude processing in a petroleum refinery was extremely dynamic and thus field monitoring attempts were made, which provides some useful information on structural integrity of column downstream equipments. The demulsifier, neutralizer, and corrosion inhibitor were mixed in crude unit at specific locations for corrosion prevention. Field monitoring includes evaluation of pH and chloride content of desalter extracted water and overhead condensed water, Base Sediment & Water (BS&W) and chloride content of as‐received & desalted crude, and iron content of overhead condensed water. Furthermore, corrosion coupon was installed in overhead section to obtain the actual corrosion rate. All the field study was conducted for a specified period. The acidity, chloride concentration, and iron loss of condensed water confirmed that acidic corrosion was under control. The corrosion rate of the installed coupons confirmed that corrosion rate was within the specified limit. The results revealed in this paper intended for refinery operators and corrosion engineers involved in understanding of actual process parameters in prevention of overhead acidic corrosion.